2022
DOI: 10.7759/cureus.28819
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Pregnant Women in Jazan, Saudi Arabia Concerning Pelvic Floor Muscle Exercises

Abstract: Introduction Weaknesses of the pelvic floor muscles in females can lead to pelvic floor dysfunction thus increasing the risk of urinary and fecal incontinence. Furthermore, its weakness can lead to reproductive organ prolapse and sexual dysfunction, and influence sexual arousal and orgasm. There is limited evidence concerning the awareness of Saudi women regarding the importance of physical activity in the prevention and treatment of pelvic floor dysfunction. The current investigation aims to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Regarding awareness of pelvic exercises, a substantial proportion of women in our study recognized their effectiveness in managing urinary leakage (185 women, 61.7%) and preventing prolapse progression (193 women, 64.3%), despite the absence of specific exercise details, such as the name of pelvic floor exercises (PFEs). This perspective is consistent with the findings reported by Derrar et al, wherein approximately one-third of women, comprising exclusively pregnant individuals, exhibited doubt about the benefits of pelvic floor muscle exercises [21]. Others reported that the women who were knowledge proficient in both POP and UI not only had knowledge of PFEs, but also performed Kegel exercises [22].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding awareness of pelvic exercises, a substantial proportion of women in our study recognized their effectiveness in managing urinary leakage (185 women, 61.7%) and preventing prolapse progression (193 women, 64.3%), despite the absence of specific exercise details, such as the name of pelvic floor exercises (PFEs). This perspective is consistent with the findings reported by Derrar et al, wherein approximately one-third of women, comprising exclusively pregnant individuals, exhibited doubt about the benefits of pelvic floor muscle exercises [21]. Others reported that the women who were knowledge proficient in both POP and UI not only had knowledge of PFEs, but also performed Kegel exercises [22].…”
Section: Discussionsupporting
confidence: 89%
“…One of the key ndings of this study is the signi cant association between educational level and practice among the pregnant women. This is similar to the study ndings conducted in Jazan where pregnant women with higher levels of knowledge were more motivated to do Pelvic Floor Muscle exercise (13). However, on the contrary there was no association between educational level and pelvic oor muscle training knowledge (p = 0.63) in a study conducted among pregnant females in Thailand (14).…”
Section: Discussionsupporting
confidence: 85%